Therapeutic Efficacy of Moxibustion with Seed-Sized Moxa-Cone at Jing Acupoint on Limb Spasticity after Stroke： A Meta-Analysis - ZHANG Jinfei; JIANG Jiahui; TANG Jiqin (康复学报)
ObjectiveTo systematically evaluate the effect of moxibustion with seed-sized moxa-cone at Jing acupoint on limb spasticity after stroke, and to provide a scientific basis for the clinical application of moxibustion with seed-sized moxa-cone.MethodsData were searched from the China Knowledge Network (CNKI), Wanfang Data, VIP, CBMdisc, China Clinical Registry, PubMed, Embase, Web of Science and Cochrane Library. The randomized controlled trials (RCTs) of moxibustion with seed-sized moxa-cone at Jing acupoints for stroke patients with spastic hemiplegia were included, and the retrieval time was from inception to July 2022. The main outcome measures included the effective rate of spasticity improvement [number of cases (fully recovered + significant effect + some effect)/total number of cases]×100%], modified Ashworth scale (MAS) grading, clinical spasm index (CSI) score, Fugl-Meyer assessment scale (FMA) score, Barthel index (BI) score. Two researchers independently conducted literature screening according to the inclusion and exclusion criteria, data extraction, quality evaluation by the Cochrane risk of bias tool. RevMan 5.3 software was used for meta-analysis. Measurement data were expressed by mean difference (MD) and standardized mean difference (SMD) with 95% confidence interval (CI), and enumeration data were expressed by odds ratio (OR); SAS studio software was used to calculate the effect size (logrr) and standard error (selogrr) of ordinal data based on the cumulative odds model. The statistical heterogeneity was assessed by probability value (P value) and heterogeneity value (I2 value). If P≥0.1 and I2≤50%, a fixed effects model would be used. If P<0.1 or I2>50%, a random effects model would be used.ResultsA total of 10 RCTs with 736 patients were included, with 368 cases in the control group and the experimental group respectively. Meta-analysis results showed that, (1) The spasticity improvement rate: compared with the control group, the effective rate of the experimental group was significantly higher [OR=3.96, 95% CI (1.25,12.53), Z=2.34, P=0.02]. (2) MAS grade: compared with the control group, the grade of spasticity of the experimental group was significantly lower [RR=3.03, 95% CI (2.08, 4.41), Z=5.78, P<0.000 01]. (3) CSI score: compared with the control group, CSI score of the experimental group was significantly lower [MD= -0.96, 95% CI (-1.26, -0.66), Z=6.20, P<0.000 01]. (4) FMA score: compared with the control group, FMA score of the experimental group was significantly higher [MD=15.17, 95% CI (7.89, 22.46), Z=4.08, P<0.000 1]. (5) BI score: compared with the control group, BI score of the experimental group was significantly higher [MD=5.95, 95% CI (4.38, 7.53), Z=7.39, P<0.000 01].ConclusionMoxibustion with seed-sized moxa-cone at Jing acupoint can effectively improve the spasticity of limbs, reduce muscle tone, improve the motor function of limbs and quality of life of patients after stroke. However, more studies and samples would be needed for further validation in order to provide more reliable clinical evidence, due to the limitations of the included literature.